Strengthening Tourism Destination Ecosystems through Interesting Promotion-Based Marketing and Simple Financial Statement Recording Training in Wates Jaya Village, Cigombong, Bogor - Muhamad Ipaludin; Restu Fauziah; Zahro Rihadatul Aisy; Sekar Ayu Ningrum; Muhamad Haikal Zibran; Rizky Pebriansyah; Alpian Mauludin; Vina Syabilla; Ari Kurniawan; Muhamad Sidiq; Maria Magdalena Melani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Strengthening the tourism destination ecosystem through marketing based on interesting promotion and training about financial reports with the aim of helping the community to develop village potential, introducing the village to the wider community and having an impact on the community's economy. Observation, interviews, mentoring and documentation are the methods used. As a result, the village community can optimize the potential of the village and student activities help develop the village. the conclusion is that community service activities play a role in helping the community introduce tourist villages that are not widely known to the outside community.